1988
DOI: 10.1111/j.1525-1470.1988.tb00904.x
|View full text |Cite
|
Sign up to set email alerts
|

Percutaneous Absorption of Hydrocortisone During and After the Acute Phase of Dermatitis in Children

Abstract: Percutaneous absorption of hydrocortisone was measured by a fourhour absorption test in !6 children duting and after the acute phase of dermatitis. In the acute phase, after the application of 1% hydrocortisone cream the increment in plasma cortisol ranged from 47 to 961 nmol per liter (median 248 nmol/L), After the acute phase the increment was significantly (P < 0,0!) lower: range 18 to 241 nmol per liter (median 95 nmol/L), In addition to local effect, topical hydrocortisone therapy of childhood dermatitis … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
47
0
2

Year Published

2008
2008
2024
2024

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 55 publications
(50 citation statements)
references
References 9 publications
1
47
0
2
Order By: Relevance
“…In AD, there already is a defective epidermal barrier (36)(37)(38), and penetration of topical corticosteroids is 2-to-10-times greater than that through healthy skin (39).…”
Section: Discussionmentioning
confidence: 99%
“…In AD, there already is a defective epidermal barrier (36)(37)(38), and penetration of topical corticosteroids is 2-to-10-times greater than that through healthy skin (39).…”
Section: Discussionmentioning
confidence: 99%
“…In a study involving young adults with atopic dermatitis, percutaneous application of 1.0% hydrocortisone cream yielded median serum cortisol levels of 125 nmol/L during the acute phase of the condition and 16 nmol/L during remission. 31 Furthermore, it has been shown that even for a lowpotency corticosteroid such as hydrocortisone, 15.0% of the dose crosses the placenta unmetabolized. 32 These studies suggest fetal serum cortisol levels in the range of 2.4-18.75 nmol/L after the application of 1.0% hydrocortisone cream to the mother's skin.…”
Section: Discussionmentioning
confidence: 99%
“…We had access to data for the period covering Jan. 1, 1996, to Mar. 31,2009. The 10th revision of the International Statistical Classification of Diseases and Related Health Problems (ICD-10) was used to code diagnostic information.…”
Section: Orofacial Clefts and Other Diagnostic Informationmentioning
confidence: 99%
“…In children with AD, percutaneous absorption of hydrocortisone was proven to be significantly lower in the convalescent phase of the disease compared with the acute phase, probably owing to the restoration of the skin barrier. 4 Several years after the introduction of hydrocortisone, new synthetic corticosteroids were developed. Synthetic corticosteroids can modulate endogenous cortisol secretion by influencing hypothalamic and pituitary effects on adrenal gland activities through the hypothalamic-pituitary-adrenal (HPA) axis.…”
Section: Discussionmentioning
confidence: 99%